Annual crop management practices in aonla for subtropical region - Pandey, Devendra; Singh, Sanjay Kumar; Poojan, Shiv; Shukla, Shardulya (Indian Horticulture, 2025)
Aonla is one of the most nutritious fruits and the second richest source of vitamin C after Barbados cherry. It is also a fair source of carotene, thiamine, riboflavin, and carbohydrate as well as minerals like iron, phosphorus, calcium and magnesium. However, the low yields of aonla might be due to lack of technical knowledge and non-adoption of aonla production technology by the farmers. The knowledge possessed by the farmers and disseminated by institutions may boost aonla production with profitability.